2021
DOI: 10.1038/s41467-021-22570-w
|View full text |Cite
|
Sign up to set email alerts
|

The VRNetzer platform enables interactive network analysis in Virtual Reality

Abstract: Networks provide a powerful representation of interacting components within complex systems, making them ideal for visually and analytically exploring big data. However, the size and complexity of many networks render static visualizations on typically-sized paper or screens impractical, resulting in proverbial ‘hairballs’. Here, we introduce a Virtual Reality (VR) platform that overcomes these limitations by facilitating the thorough visual, and interactive, exploration of large networks. Our platform allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…As the size and complexity of PPI networks increases, more efficient visualization algorithms are needed ( Chong, Wishart and Xia, 2019 ; Koutrouli et al, 2020 ). Augmented reality technologies and virtual reality (VR) remove the constraints of 2D/3D space constraints ( Pirch et al, 2021 ; Hütter et al, 2022 ). Moreover, the notable advances in the prediction of the structure of proteins from their sequence in amino acids with alphafold ( Jumper et al, 2021 ), which could lead to a revolution in the PPI prediction algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…As the size and complexity of PPI networks increases, more efficient visualization algorithms are needed ( Chong, Wishart and Xia, 2019 ; Koutrouli et al, 2020 ). Augmented reality technologies and virtual reality (VR) remove the constraints of 2D/3D space constraints ( Pirch et al, 2021 ; Hütter et al, 2022 ). Moreover, the notable advances in the prediction of the structure of proteins from their sequence in amino acids with alphafold ( Jumper et al, 2021 ), which could lead to a revolution in the PPI prediction algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…VRNetzer ( Pirch et al, 2021 ) facilitates large biological and protein interaction network exploration, overcoming the often dense “hairballs” that are typical of such an analysis. ProteinVR ( Cassidy et al, 2020 ) is a web-based tool that can visualise PDB protein structures on multiple devices using WebXR that gives useful biological context and allows users to situate themselves in 3D space.…”
Section: Applicationsmentioning
confidence: 99%
“…Most existing visualization approaches support static overviews of the entire graph [18,20] and interactive views of focused subgraphs [1,11,40]. However, research has shown that the inherent multi-scale nature of biological graphs can only be fully appreciated when the entire range from local to global graph structures can be inspected continuously and interactively [32]. Some tools such as Reactome [35] strike a balance by displaying overviews of biological graphs as well as detailed views of selected subgraphs or pathways.…”
Section: Related Work 21 Biological Graph Visualizationmentioning
confidence: 99%